Persepsi tenaga kesehatan tentang praktek kolaboratif di puskesmas bojong kabupaten purbalingga - Karisma Nur Insani; Dedy Purwito (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: to identify the perception of health workers about collaborative practices in the Bojong Primary Health Care in Purbalingga Regency. .Methods: This article is a qualitative study with a phenomenological approach. used the Snowball technique (Non probably sampling). Data collection using interviews with 9 participants consisting of 6 key informants and 3 general informants with the characteristics of the age of the informant is more than 30 years. working time is more than the same as 5 years.Results: This study shows there were various perceptions of health workers about collaborative practices at the Bojong Primary Health Care in Purbalingga District. The researcher divides into 6 themes which include interprofessional relations, effective communication, the role of leaders, lack of human resources, changing roles, and workload.Conclusion: Health workers agree that collaborative practice is closely related to interpersonal relationships between health workers. Supporting factors in collaborative practice are effective communication, and the role of the leader. Then the inhibiting factors of collaborative practice are lack of human resources, changing roles and workload.